2010
DOI: 10.1159/000321322
|View full text |Cite
|
Sign up to set email alerts
|

Disposition and Metabolism of Ralfinamide, a Novel Na-Channel Blocker, in Healthy Male Volunteers

Abstract: Ralfinamide is an α-aminoamide derivative with ion channel blocking properties, acting both peripherally and centrally through different molecular targets important in pain control. Absorption, blood and plasma time courses, and urinary and faecal excretion of total radioactivity were assessed in 6 male healthy volunteers administered a single oral dose of 320 mg 14C-(S)-ralfinamide. Pharmacokinetics of the parent drug were investigated over 120 h, urinary and plasma metabolites up to 192 h post-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…N-dealkylation was postulated as a major metabolic pathway also for ralfinamide, an α-aminoamide derivative analogue of safinamide [19]. …”
Section: Discussionmentioning
confidence: 99%
“…N-dealkylation was postulated as a major metabolic pathway also for ralfinamide, an α-aminoamide derivative analogue of safinamide [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Data from animal models of inflammatory and neuropathic pain have suggested that ralfinamide exhibits a significant analgesic effect while also having a well-tolerated safety profile [6,7,8]. Moreover, ralfinamide is the only small molecule drug in a late-stage clinical trial for the treatment of neuropathic pain [9,10,11,12,13]. However, the anti-allodynic efficacy and Nav1.7-selectivity of ralfinamide need further improvement.…”
Section: Introductionmentioning
confidence: 99%
“…However, achieving selectivity for specific subtypes with small-molecule inhibitors has been challenging [19,20]. α-Aminoamide derivatives such as ralfinamide were previously developed as potential drug candidates for the specific treatment of neuropathic pain [21,22]. Studying the relationship between target selectivity and potency for novel α-aminoamide derivatives is critically needed.…”
Section: Discussionmentioning
confidence: 99%